Romanisierung als Schritt zur „Modernisierung” des Mazedonischen - Mladin, Constantin-Ioan (Linguistik Online, 2017)
This investigation aims to outline the contribution that Romanic languages had to the finalization of the configuration of the modern Macedonian language, both in terms of common language and of technical terms. More specifically, the paper aims: 1) to identify Romanic idioms that have influenced to some extent the Macedonian language, either indirectly (through another language such as French, Italian, Spanish, or Portuguese) or directly (through Romanian – Dacoromanian and Aromanian, or through Meglenoromanian); 2) to show the specific historic context and the means through which various elements from the Romanic linguistic sphere were imported into Macedonian; 3) to evaluate the quantitative share of loans (in vocabulary and terminology); 4) to indicate the areas of activity that have been affected by the infiltration of Romanic lexical items. Even if loans from Romanic languages are not very frequent in the common standard language, the Macedonian language being relatively conservative and refractory with regards to non-Slavic influences, these are perceived as a sign of emancipation and modernity, in contrast to the old Turkish basis, the existence of the Romanic lexical and terminological basis also illustrating the tendency for this language to differentiate itself from its two Slavic neighbors, the Bulgarian and the Serbian languages. At the same time, the infusion of Romanic words and terms has contributed significantly to the “modernization” of the Macedonian language, particularly with regards to its meta-dialectal unification and to its coming closer to major languages of great circulation and great cultural prestige.